Silk and religion : an exploration of material life and the thought of people, AD 600-1200 - Liu, Xinru (Oxford University Press, 1996)
The author studies the silk trae in Eurasia between the seventh and twelfth centuries to explore how religious ideas and institutions affected economic behaviour. Long-distance silk trade had been established for centuries in ancient Eurasia, well before the state in Tang China and the Byzantine Empire set up state silk industries and clothing codes to regulate the trade and consumption of silk textiles.